Global Development Finance 2004 Harnessing Cyclical Gains for Development. (Washington World Bank Publications, 2004)
Annotation This World Bank publication presents analysis and commentary on recent developments in international finance for 150 developing countries, and statistical tables on the external debt of 138 countries.
Scholarly & Professional
Keywords: Electronic books